(untitled) (LEARNing Landscapes, 2021)
The COVID-19 pandemic has required educators at all levels to pivot instruction online. In this article, we consider methods we adopted to engage novice science teachers in approximations of teaching, online. We describe the principles of our science teacher education program and provide a rationale for the core feature of our science teaching methods course: practice-based pedagogy. We then discuss adaptations we have made to engage novices in ambitious science teaching practices online, and the affordances and constraints the virtual context posed to these practices. We conclude with a discussion of considerations for online practice-based pedagogy.